BAK-SNEPPEN MODELS FOR THE EVOLUTION OF STRUCTURED KNOWLEDGE - Piccinini, Livio Clemente; Chang, Ting Fa Margherita; Lepellere, Maria Antonietta; Taverna, Mario; Tubaro, Giovanni (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Scientific knowledge is subject to a twin evolution, since its development towards novelty creates disconnections and inconsistencies, while the need of structure requires order and method so that transmission and comprehension can be ensured. Models of biological evolution can help to understand many social and economical phenomena where the search for optimality is hindered by voluntary or random competition. Bak-Sneppen is one of the most significant models because it balances at best explication power and simplicity. Unlike cellular automata models, Bak-Sneppen models join locality and globality. The authors try to re-read these models in the framework of mathematics, where, despite its high developped structure, knowledge waves can hinder comprehension both of pupils and of scholars. Some paradoxes are shown, where a greater knowledge diminishes efficiency and capability.